Electrophysiology of Scorpion Peg Sensilla - Knowlton, Elizabeth D. (MyJove Corporation, 2011)
We describe a modification of an existing tip-recording technique(1,2) for electrophysiologically investigating short, peg-like sensory sensilla(3,4). On the mid-ventral surface of all scorpions are two appendages called pectines, which have dense fields of mechano- and chemosensory peg sensilla(5,6). One method for assessing chemoresponsiveness of these sensilla uses a tungsten electrode for extracellularly recording neural activity within a sensillum as a volatile odorant is introduced to the sensory field(5,7). The limitations of this method include slow data collection and uncontrolled stimulant introduction to, and removal from, the peg field. To overcome these limitations, we developed a new tip-recording technique that uses nonpolar mineral oil as a medium through which to deliver water-based tastants to individual peg sensilla(8,9). We have successfully applied this method to obtain sensillar chemoresponses to citric acid, ethanol, and salt. Here we describe the experimental protocol for such a study(9). We think this new method may be useful for studying the response properties of other arthropod chemosensory systems, including those of insects(10, 11) and crustaceans(12).